(untitled) (Innovative professional education, 2025)
The article examines modern computer technologies used for organizing distance learning in vocational and technical education institutions (VETIs). The main tools, such as cloud platforms, virtual laboratories, gamification, adaptive learning, and artificial intelligence, are analyzed. Their role in improving accessibility, efficiency, and quality of the educational process is emphasized. The experience of educators in implementing these technologies and their impact on the formation of professional competencies is also discussed.